Diagnostic strategies used in primary care. (20th April 2009) - Heneghan, C; Glasziou, P; Thompson, M; Rose, P; Balla, J; Lasserson, D; Scott, C; Perera, R
Abstract : The strategies used by general practitioners in making a diagnosis are being formally recognised; this article is the first in a series that will illustrate their application, and is accompanied by a case study (doi:10.1136/bmj.b1187 )